EP334/#194 Single cell transcriptomic analysis of a low grade serous ovarian cancer patient treated with pressurized intraperitoneal aerosolized chemotherapy (PIPAC). (4th December 2022) - Dellinger, Thanh; Bishara, Isaac; Cosgrove, Patrick; Majumdar, Sumana; Kohut, Adrian; Tinsley, Raechelle; Eng, Melissa; Frankel, Paul; Chang, Sue; Solass, Wiebke; Cristea, Mihaela; Raoof, Mustafa; et al.
Abstract : Objectives: Low grade serous (LGS) ovarian cancer (OC) patients with recurrent peritoneal metastases (PM) have poor prognoses due to inherently chemo-resistant tumors. PIPAC is an intraperitoneal (IP) treatment that intensifies chemotherapy delivery to PM via drug nebulization and pressurization. We analyzed the molecular and tumor microenvironment (TME) changes of a PIPAC-treated LGS patient. Methods: A heavily pretreated, recurrent LGS OC patient underwent PIPAC (aerosolized cisplatin 10.5 mg/m2 and doxorubicin 2.1 mg/m2, at 12 mmHg), via laparoscopy q6 weeks, for two cycles (NCT04329494 ). Tumor and normal peritoneum were biopsied immediately before and after each PIPAC. After cancer cell and nuclei isolation, sc-RNAseq was performed. 10X Genomics generated cDNA libraries were sequenced on Illumina HiSeq 2500 or NovaSeq 6000 instruments using 150 cycle paired-end sequencing at a depth of 10K reads/cell. Multiplex immunohistochemistry (IHC) was performed (quad staining PAX5-DAB/PD-L1/CD68/Tryptase; triple staining PD-1/CD8/CD3; double staining FOXP3-DAB/PD-1). Results: The Peritoneal Carcinomatosis Index (PCI) reduced from 20 to 14 after one cycle. scRNAseq of post-PIPAC tumors demonstrated significantly upregulated immune and KRAS signaling pathways, compared to post-PIPAC normal tissues. Acute PIPAC-induced responses included upregulation of immune pathways (inflammatory response, complement, interferon-gamma response), hormonal signaling (androgen, estrogen late response), TNF-a signaling via NF-kB, apoptosis, and hypoxia pathways. PD-1 expression was increased in tumor infiltrating lymphocytes (TILs) within cancer islands. Conclusions: PIPAC induces peritoneal tumor regression in LGS OC, possibly via modulation of TME, and upregulation of immune and KRAS signaling pathways; thus suggesting potential future combination with MEK inhibitors and immunotherapies.